Digitalization and income inequality: Evidence from households - Shu Tian; Yu Wu; Wenwen Zhou (Asian Development Bank (ADB), 2025)
By capturing the adoption of digital services and applications as well as digital industry development, this paper constructs a comprehensive index to measure digitalization at the city level in the People's Republic of China (PRC) and investigates the impact of digitalization on income inequality using household-level data in the PRC. The findings reveal that a one-unit advancement in the digitalization index significantly reduces the income gap by 1.83% for an average household. This mitigating effect remains statistically and economically significant after addressing endogeneity and robustness concerns. The impact is more pronounced in less-developed areas and among households with lower education levels. Further analysis shows that digitalization narrows the income gap by increasing earnings more for lower-income households, primarily through enhanced employment and investment opportunities. Additionally, digitalization boosts business income for entrepreneurial households. These findings provide valuable policy insights, suggesting that developing economies can reduce income inequality by promoting digitalization, supporting digital-related job creation, and enhancing financial literacy.
Keywords: D30; O10; O30; 330; digitalization; inclusiveness; income inequality